A scientific note on the Italian Mini BOTs and the proposal of the CCCFs - Alessandro Saccal (Economics and Econometrics Research Institute (EERI), 2024)
This note shows that the Italian Mini BOTs proposed in 2019 bore the potential neither to become Italian legal tender nor to practically increase Italian government debt, but to practically cause a mere reduction in taxation and thence in government spending or transfers. Since the Eurozone practically excluded an increase in government debt or a monetisation of that which the Italian treasury owed certain firms the Italian Mini BOTs, precisely because of the probable uncertainty associated with them, would have (i) stimulated expenditure more than a taxation rebate to the said firms and (ii) facilitated Italy's hypothetical abandonment of the Eurozone and return to sustained and consistent growth thereby, seemingly being the one and only reason for which all of their critics opposed them. This note in fact proposes the direct emission of Italian taxation credit certificates endowed with a further reduction in taxation conditional on their use for consumption, termed "Certificati a Consumo di Compensazione Fiscale", thereby attaining to the said two ends as well as to that of alleviating the liquidity shortage on the part of firms and the private sector at large without recourse to monetary policy.
Keywords: E19; E42; E44; E51; E52; E58; E61; E62; E63; E65; G21; G23; G28; H20; H30; H50; H60; 330; CCCFs; government budget constraint; government debt; government spending; Italian Mini BOTs; miniature treasury bills; money supply; public finance; taxation; taxation credit certificates; transfers